2007
DOI: 10.2169/internalmedicine.46.6208
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma Arising in a Mediastinal Enteric Cyst

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A review of the published English literature revealed just four cases of mediastinal enteric cyst in atypical locations (ie, other than the right posterior mediastinum). Of these four cases, two were left posterior mediastinal masses [3,4]; one was in the middle mediastinum, mimicking a pericardial cyst; and one was in the anterior mediastinum [5,6]. However, although Carr and colleagues [6] reported an enteric cyst in the same position as in our case (ie, anterior mediastinum) in 1977, CT technology was unavailable at that time, and hence diagnosis was not possible.…”
Section: Commentmentioning
confidence: 60%
“…A review of the published English literature revealed just four cases of mediastinal enteric cyst in atypical locations (ie, other than the right posterior mediastinum). Of these four cases, two were left posterior mediastinal masses [3,4]; one was in the middle mediastinum, mimicking a pericardial cyst; and one was in the anterior mediastinum [5,6]. However, although Carr and colleagues [6] reported an enteric cyst in the same position as in our case (ie, anterior mediastinum) in 1977, CT technology was unavailable at that time, and hence diagnosis was not possible.…”
Section: Commentmentioning
confidence: 60%
“…Foregut cysts, which include bronchogenic, esophageal, and enteric cysts, make up 18% of all primary mediastinal masses (1). Mediastinal enteric cysts account for only 1-2% of all mediastinal cysts (2).…”
Section: Introductionmentioning
confidence: 99%
“…3 Approximately 10% of duplication cysts contain ectopic gastric mucosa, usually at the wall of the duplications. [4][5][6] Enteric cysts usually lie in the posterior mediastinum and, in most instances, have no connection with the esophagus. 7 The predominant mechanism of 99m Tc-pertechnetate uptake is specific mucin cell uptake and secretion.…”
mentioning
confidence: 99%
“…Approximately 7% to 20% of enteric cysts are found in the thorax, 2 whereas only 1% to 2% of all mediastinal cysts are enteric cysts 3. Approximately 10% of duplication cysts contain ectopic gastric mucosa, usually at the wall of the duplications [4][5][6]. Enteric cysts usually lie in the posterior mediastinum and, in most instances, have no connection with the esophagus 7.…”
mentioning
confidence: 99%